MEMBUAT TRAINER KIT SUZUKI SMASH TITAN "SISTEM PENGAPIAN" - , NICKO ANHAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Technological development cannot be separated from the influence of development in electronics or electricity sector, then the development in electronics or electricity sector influences the word, especially in automotive field. Automotive field in closely related to the electricity system. It can be seen from the components of vehicles supported by electricity system. Therefore, i make pratical tools function to learn electricity system of motorcycle in the from of training kit electricity system of Suzuki Smash Titan. In making this training kit is used several methods to obtain the accurate data source. The methods used are first, observation directly to the field, interview and library study. The second is planning, the third is making training kit and than analyst and trial. The result of the study shows that a training kit can be applied as good. is can understand the working principles of the ignition and charging system Suzuki Smash Titan. Therefore, the it is expected the tool will be useful for students who will learn more on the electricity system.